Effect of CAD-CAM block thickness and translucency on the polymerization of luting materials - Bengü Doğu Kaya; Selinsu Öztürk; Ayşe Aslı Şenol; Erkut Kahramanoğlu; Pınar Yılmaz Atalı; Bilge Tarçın (BMC, 2024)
Abstract Aim This in-vitro study aimed to evaluate the degree of conversion (DC) of dual-cured luting cement (Bifix QM, VOCO) and flowable composite (Grandio Flow, VOCO) under lithium disilicate glass-ceramic (IPS e.max CAD, Ivoclar Vivadent) and hybrid ceramic (Grandio Blocs, VOCO; Cerasmart, GC) CAD-CAM blocks with different thicknesses. Materials and methods Contrast ratio (CR), translucency (TPab, TP00), and opalescence (OP) parameters of 30 disc-shaped CAD-CAM blocks (n = 5) prepared with two different thicknesses (1.5 and 2 mm) and 8 mm diameters were calculated using a spectrophotometer (VITA Easyshade V, Zahnfabrik). A total of 36 Bifix QM and Grandio Flow samples were prepared at 100 μm thickness using a specific setup by polymerizing from the top of the blocks. Following immersion in distilled water at 37 °C for 24 h, luting materials were examined by Fourier Transform Infrared Spectroscopy for DC calculation. Data were analyzed using One-way ANOVA, Kruskal Wallis, Mann Whitney U, and Independent Samples t-tests (p < 0.05). Results It was observed that, as the block thickness increased TPab, TP00, and OP decreased, while CR increased. There was no significant difference between the DC of Bifix QM and Grandio Flow when 1.5 mm blocks were used in all groups (p > 0.05). DC of Grandio Flow was significantly higher than Bifix QM under 2 mm-IPS e.max CAD (p = 0.011). Conclusion The translucency of the CAD-CAM blocks varies depending on their thickness. However, there was no significant difference in the DC of the luting materials depending on the block thickness. Further studies are needed on the use of flowable resin composites as luting material.